Semantik Idiom Bahasa Inggris Yang Menggunakan Leksem Apple - Rizky Ainun Maftuhah; Mulyadi (Center of Language and Cultural Studies, 2023)
Idiom is a language unit whose meaning cannot be predicted from the structure that composes it. In English idioms, many idioms use elements of fruit names. The author takes the apple lexeme to be the object of research. This is because many English idioms use the apple lexeme. In this study, researchers will focus on lexical meaning and idiomatic meaning in idioms that use apple lexeme and the idiom patterns that compose them. The research method used is a qualitative descriptive method which is divided into two stages, namely the data collection stage and the data analysis stage. The results obtained from this study are the lexeme apple has food to describe a person, and there are three patterns that form idioms using the lexeme apple, namely 1) adjective + apple; 2) apple + noun; 3) noun + apple